Climate Change Capital - MacDonald, Greg; Elias, Jaan (London : Yale School of Management, 2019)
In 2004, James Cameron and some colleagues created the Climate Change Capital, a firm designed to marshal private capital in order to help fight climate change. Climate Change Capital recruited fund managers from London's financial sectors however, these finance professionals had a very different culture and attitude to the employees, who had created the firm.
Originally Published InMacDonald, G., & Elias, J. (2019). Climate Change Capital. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cameron, James; Climate Change Capital -- Case studies; Climatic changes -- Economic aspects -- Case studies; Business enterprises -- Environmental aspects -- Case studies